Water quality assessment of Narmada River along the different topographical regions of the central India. Issue 1 (1st January 2020) - Gupta, Deepak; Shukla, Reetika; Barya, Mahesh Prashad; Singh, Gurudatta; Mishra, Virendra Kumar
ABSTRACT: This study was performed to assess water quality in the Narmada River, the third-longest river in India. Water samples were collected from 6 major sampling stations with 17 sampling points. Nine water quality parameters were analyzed to calculate the water quality index (WQI), followed by multivariate statistical evaluation. The results indicated that water quality in the upper Narmada varied from excellent to very poor – comprising excellent for approximately 12%, good for 17%, poor for 59%, and very poor for 12% of pre-monsoon samples, but excellent for 17%, good for 12%, and poor for 71% of post-monsoon. While the general water quality in the Narmada was poor, anthropogenic inputs such as domestic sewage and agricultural runoff influenced some parameters – e.g. BOD, nitrate, and total coliform. More studies are required for completing water quality evaluation.